2018
DOI: 10.1097/aud.0000000000000465
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency Distortion-Product Otoacoustic Emission Repeatability in a Patient Population

Abstract: HF DPOAEs were repeatable across four test trials for all three paradigms measured in a group of CF patients. These results are encouraging for the measurement of HF DPOAEs to be monitored in those exposed to ototoxic agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 51 publications
2
22
0
1
Order By: Relevance
“…In adults and children at the highest frequencies tested (up to 16 kHz), average noise floors are less and DPOAE levels are higher than were recorded in the current study [5,[48][49][50]52]. The testing environment for the current study also could have contributed to overall higher noise floors than previously recorded in clinical and patient rooms where it was only the tester and the patient [51,53]. Often, family members in addition to the parents were present during testing, as were nursing staff.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…In adults and children at the highest frequencies tested (up to 16 kHz), average noise floors are less and DPOAE levels are higher than were recorded in the current study [5,[48][49][50]52]. The testing environment for the current study also could have contributed to overall higher noise floors than previously recorded in clinical and patient rooms where it was only the tester and the patient [51,53]. Often, family members in addition to the parents were present during testing, as were nursing staff.…”
Section: Discussionmentioning
confidence: 61%
“…If only frequencies between 10 through 16 kHz are examined for newborns, the average absolute difference between trials was 2.82 (SD = 2.68) for FPL and 3.43 (SD = 2.62) for SPL calibrations. These results are less variable than for young, normal-hearing adults using SPL calibration [5] and more variable than cystic fibrosis patients monitored between ototoxic treatments using alternate calibration techniques [51] with average absolute differences between trials of 5.15 (SD = 4.40) and 1.96 (SD = 2.19), respectively. It should be noted that the newborns in this study only had DPOAEs measured in one session compared to the other literature referenced for comparison which involved data collection minimally across several hours, but more often at least two different days.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…It has also been demonstrated that higher frequency (>8 kHz) information is most valuable for timely detection of cochlear dysfunction and specifically utilizing high-frequency DPOAEs [16,27]. Furthermore, the feasibility of measuring DPOAEs beyond 8 kHz has been demonstrated across a range of ages (10 to 65 years) with normal-hearing [21] as well as repeatable over time in healthy, young, normal-hearing adults and in a patient population not exposed to ototoxic medications during monitoring [28][29][30].…”
Section: Advancing Distortion Product Otoacoustic Emission (Dpoae) Pamentioning
confidence: 99%